Study of maternal and neonatal outcomes of placenta accreta spectrum in a tertiary care hospital - Naser, Ashitha; Praveen, Veena; Kurian, Simi; S, Ajith (Asian Journal of Medical Sciences, 2023)
Background: Placenta accreta produces significant maternal morbidity and mortality. A detailed knowledge of outcome is needed to develop a standardized risk appropriate maternal care system. Aims and Objectives: The aim of the study was to study the maternal and neonatal outcome of women with placenta accreta spectrum (PAS) in a tertiary care hospital. Materials and Methods: A hospital-based prospective observational study was conducted among the 40 women with PAS during a period of 3 years. Exposure factors such as previous caesarean sections, previous uterine procedures, and present or previous placenta previa; maternal outcome factors include obstetric hysterectomy, massive blood transfusion, bowel and bladder injury, and death; neonatal outcome factors include prematurity, newborn intensive care unit (NICU) admissions, APGAR scores, and birth weight. The data were analyzed by calculating frequency and percentage. Results: Of the 40 cases studied, 25 were known cases of PAS, and the remaining was diagnosed intraoperatively. About 90% (36 cases) underwent an obstetric hysterectomy. In 62.5% of patients, large vessel ligation and a clamp were applied. About 32.5% of patients required massive blood transfusions, 20% sustained bladder injuries, and there was 1 maternal death. About 76% of babies born to mothers with PAS were preterm, 43% required NICU admission, and there were 5 neonatal deaths (12%). Conclusion: The PAS is associated with significant maternal morbidity in the form of severe postpartum hemorrhage requiring massive blood transfusions and bladder injury. There is also increased neonatal morbidity and mortality. Hence, there is a need for early termination in anticipation of grave complications.